1991
DOI: 10.1038/349243a0
|View full text |Cite
|
Sign up to set email alerts
|

Human IgE, IgG4 and resistance to reinfection with Schistosoma haematobium

Abstract: A well recognized feature of the immune response to parasitic helminth infections, including schistosomiasis, is the production of large amounts of specific and nonspecific IgE1,2. Immunological pathways involving IgE can lead to damage to the developing schistosomulum and it has been suggested that responses involving IgE could have evolved as protection against helminth infections. There has been no epidemiological evidence to support this idea and the only significant IgE responses known in man are those in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

49
438
4
7

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 610 publications
(498 citation statements)
references
References 23 publications
49
438
4
7
Order By: Relevance
“…One aspect which would need to be pursued is the whole question of immunity. Information is now accumulating on the determinants of immunity under different situations (Hagan et al 1991), and it is likely that differences in the immunity to infection in different areas could partly account for differences in observed aggregation. For example in Burundi, Cohoha Lake exhibited a much higher degree of parasite aggregation than the Rusizi Plain.…”
Section: Discussionmentioning
confidence: 99%
“…One aspect which would need to be pursued is the whole question of immunity. Information is now accumulating on the determinants of immunity under different situations (Hagan et al 1991), and it is likely that differences in the immunity to infection in different areas could partly account for differences in observed aggregation. For example in Burundi, Cohoha Lake exhibited a much higher degree of parasite aggregation than the Rusizi Plain.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] Parallel results have also been obtained in a S. haematobium-infected population. 11,12 We previously found in a Malian population that one polymorphism in the IL13 gene, rs1800925(C/T) (also called IL13-1055C/T or IL13-1112C/T), was associated with susceptibility to S. haematobium infection. 12 This result was confirmed in an independent study performed in Kenya.…”
Section: Introductionmentioning
confidence: 99%
“…Repeating treatment after 3-6 weeks could help deal with the problem, but it is not an approach that has (so far) been feasible for mass deworming campaigns. A related concern is that treatment with praziquantel might lead to susceptibility to re-infection (Hagen et al, 1991), although there is some evidence that praziquantel may actually trigger a degree of immunity (Vereecken et al, 2007). Dunne et al (1992), Satti et al (1996) and Karanja et al (2002) have suggested that immunity to infection from S. mansoni can develop in some groups as a result of high antibody levels immediately following treatment (i.e.…”
Section: Deeper Deworming Doubtsmentioning
confidence: 99%